Analyze the Effects of Indian Population on Economy of India - Shekhar Wadia, Dr Rakesh Yadav, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research is based on population of India and the Indian economy. The population of India is 1,366,417,754 in 2019. Like as the economy of India is 2.8 trillion dollars in 2019. In this research paper, we will compare the economy and population of India. When we divide the economy of India in Indian population, its 2.31 lakhs per capita with simple random sampling. But Indian economy is not dividing fairly. Using stratified random sampling [1,2] finding the strata of total population of India as compare to economy of India.